Empowering family resilience: Muslim women’s impact in Perbaungan - Arifianti, Sari Maharani; Nasution, Yenni Samri Juliati; Atika, Atika (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
This study aimed to explore the contributions of women in Melati I Village, Perbaungan District, who engage in trade to support their family economy. The objective was to examine how these women manage the dual roles of working while maintaining their household responsibilities. A qualitative research methodology was employed, with data collected through semi-structured interviews involving five respondents. The findings indicated that women worked for a variety of reasons, including self-development, social engagement, and economic necessity. Their participation in work had a positive impact on the family's financial stability, but also posed challenges, particularly in balancing time between work, family, and community obligations. The study revealed that despite the difficulties, women were able to manage these dual roles through strategies such as open communication with their husbands, maintaining a balance between their domestic and public responsibilities, and ensuring that their work aligned with Islamic values, which emphasize the preservation of their honor and fulfillment of household duties. The research concluded that with the right strategies, women could make significant contributions to the family economy without compromising family relationships or societal values. These findings underscore the importance of further empowering women in the family economy to enhance their potential in strengthening family economic resilience.